COMPARAÇÃO ENTRE SISTEMA DE PRODUÇÃO PUXADO E EMPURRADO: JOGO DE MONTAGEM DE CASAS COM BLOCOS LEGO - Viana, Marina Ribeiro; Tavares, Jamile Maria Araujo; Carvalho, Kristiane da Silva; Carvalho, Isadora Andrade; Santos Junior, Jorge Luiz Dantas; Santos, Paulo Ricardo Ramos; Santos, Débora de Gois (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The realization of didactic games facilitates the understanding of concepts and makes learning more pleasurable. This article presents a game of House with Lego System®, that contributed to the teaching/learning, to compare the differences between production systems pulled and pushed. This paper also involves associated concepts as demand, storage of materials and construction layout. The game was divided into five steps and each were assembled six houses for group. Along the simulations, it was checked the quality and duration of each simulation of production system. As a result, the calculation of the productivity index allowed to diagnose the production according to the characteristics of each stage. With this, it has verified that the duration of the pushed production system was lower of that pulled system. Thus, the application of the didactic game possibility compares these main characteristics of the production systems researched.